2018
DOI: 10.3329/bjid.v4i1.37673
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Hepatitis B and C Viral Infection among the Medical Waste Handlers

Abstract: Background: Chronic viral hepatitis is a major health problem worldwide. Medical waste handlers (MWH) are particularly vulnerable to such hepatitis due to nature of their job. Objective: The purpose of the present study was to see the prevalence of hepatitis B virus and hepatitis C virus infection among the medical waste handlers. Methodology: This cross-sectional study was done from January 2015 to June 2015 to know the frequency Hepatitis B and Hepatitis C among medical waste handlers in SSMC Mitford Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Commonly, medical waste handlers who are working in the collection, transportation, cleaning, and disposal of medical wastes are vulnerable to HBV, HCV, and HIV infection particularly in developing countries 14, 15 . According to previous reports, the medical waste handlers were infected by HBsAg (20.4%) in Ethiopia 1 , HBsAg (1.3%) and HCV (0.7%) in southern Ethiopia 16 , HBsAg (2.3%) and HCV (2.7%) in Tripoli, Libya 15 , 1.59% for HBsAg in Palestine 17 , 6.3% for HBV and 1% for HCV in Bangladesh 18 , and HIV (5%) in Africa 19 . A study conducted previously in Yemen on 388 public health center cleaners (PHCCs) by Al-Marrani and Al-Shamahy reported that HBV and HCV were detected in 32 (8.2%), and 4 (1.03%) of them respectively.…”
Section: Introductionmentioning
confidence: 95%
“…Commonly, medical waste handlers who are working in the collection, transportation, cleaning, and disposal of medical wastes are vulnerable to HBV, HCV, and HIV infection particularly in developing countries 14, 15 . According to previous reports, the medical waste handlers were infected by HBsAg (20.4%) in Ethiopia 1 , HBsAg (1.3%) and HCV (0.7%) in southern Ethiopia 16 , HBsAg (2.3%) and HCV (2.7%) in Tripoli, Libya 15 , 1.59% for HBsAg in Palestine 17 , 6.3% for HBV and 1% for HCV in Bangladesh 18 , and HIV (5%) in Africa 19 . A study conducted previously in Yemen on 388 public health center cleaners (PHCCs) by Al-Marrani and Al-Shamahy reported that HBV and HCV were detected in 32 (8.2%), and 4 (1.03%) of them respectively.…”
Section: Introductionmentioning
confidence: 95%
“…WHO gives a prevalence rate of 1.0% for hepatitis C, with a previously reported increase from 2.3% to 2.8% between 1990 and 2005, according to the Global Burden of diseases, injuries, and risk factors 2010 (26,27) . Many studies have revealed an increasing prevalence of hepatitis B amongst specific risk groups like medical waste handlers, blood donors, and reproductive age (5,28,29) . Amongst the developing world, a hand full of countries are exhibiting a gross decline in chronic viral infections prevalence, like Bangladesh is showing a decreasing trend of prevalence towards chronic viral infections, with rates of 0.2% to 0.7% in recent studies (30,31) .…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis B virus (HBV) and hepatitis C virus (HCV) are chronic diseases with severe health complications and a worldwide prevalence of 248 million and 71 million respectively (1)(2)(3)(4) . Approximately more than 500 million individuals suffer from hepatitis B and hepatitis C infections rendering it a leading global health dilemma (5) . According to the World Health Organization (WHO) annual proportion of individuals suffering globally from hepatitis B infection is 2 billion (4,6) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps, the results of these combined efforts and the enforcement of use of Personal Protective Equipment (PPE) such as gloves, masks and safety boots among waste collectors in Penang Island is beginning to yield positive results. Further, the overall prevalence of hepatitis C among Bangladeshi population -where majority (75%) of our respondents were from, has been previously reported to be as low as 0.2% [20] in the general population, 1% among medical waste handlers [21], and as high as 24.8% among injecting drug users (IDUs) [22].…”
Section: Prevalence Of Hepatitis C Infectionmentioning
confidence: 99%